Current and future trends of silk fibroin-based bioinks in 3D printing - Oliveira, Joaquim M. (2020)
Demographic changes are demanding for novel technological solutions in order to address the paradigm shifts of precision medicine, 3D cell culturing research, and 3D printing. Finding the adequate biomaterial/bioink and biofabrication method is a difficult and complex process, but silk fibroin bioinks are now playing an important tool kit in Bio 3D printing and tissue engineering. Due to the versatile composition of silk fibroin, different gelation methods are being explored. Herein, the recent reports and advances related to the different silk fibroin bioinks and applications, in particular the enzymatic-crosslinked bioinks, are briefly overviewed.